Encephalopathy and seizure activity in a COVID-19 well controlled HIV patient. (2020) - Haddad, S.; Tayyar, R.; Risch, L.; Churchill, G.; Fares, E.; Choe, M.; Montemuro, P.
Abstract: A 41-year-old male with a history of well controlled HIV presented with confusion and was found to have COVID-19. Lumbar puncture was negative. He had worsening encephalopathy with tonic-clonic seizure requiring intubation. He was treated with hydroxychloroquine and azithromycin with improvement in mental status back to baseline after 6 days.